TEKNIK TOKEN ECONOMIC UNTUK MENINGKATKAN KEMAMPUAN KONTAK MATA ANAK AUTIS - HERLIYANTI, ARINDA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT In social interaction, contact and relationship between one individual to the other always happened, the autism children had disturbance in their social development. The autism children had difficulty doing contact eyes to their speaking partners. The children showed failure making interpersonal relation which was indicated by the lack of response toward people around them. Because of the disturbance to the contact eyes it would disturb the children’s activities in learning and social life. The purpose of this research was to prove whether there was influence of token economic technique to enhance the contact eyes of the autism children in SDN Sedati Agung No. 402 Sidoarjo or not. The kind of this research was experiment with single subject research (SSR) and A-B design. The subject was one autism child in SDN Sedati Agung No. 402 Sidoarjo who had disturbance in holding contact eyes during interacting with the speaking partner. Based on the analysis done it indicated that to baseline phase (A) the subject did contact eyes 8-13 times with total duration 13-16 seconds for 15 minutes and to intervention phase (B) it averagely enhanced 10-15 times with total duration 14-25 seconds for 15 minutes. Based on the data analysis and the discussion it could be concluded that token economic technique could enhance the social interaction of autism children which it was done 8-13 times with total duration 13-16 seconds before, it was enhanced to be 10-15 times with total duration 14-25 seconds for 15 minutes.   Keywords: token economic technique, contact eyes